2022
DOI: 10.1038/s41598-022-06226-3
|View full text |Cite
|
Sign up to set email alerts
|

ILF2 enhances the DNA cytosine deaminase activity of tumor mutator APOBEC3B in multiple myeloma cells

Abstract: DNA cytosine deaminase APOBEC3B (A3B) is an endogenous source of mutations in many human cancers, including multiple myeloma. A3B proteins form catalytically inactive high molecular mass (HMM) complexes in nuclei, however, the regulatory mechanisms of A3B deaminase activity in HMM complexes are still unclear. Here, we performed mass spectrometry analysis of A3B-interacting proteins from nuclear extracts of myeloma cell lines and identified 30 putative interacting proteins. These proteins are involved in RNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…If a protein had more than one BP and one CC, the term with a larger population was selected to represent it in the network ( Table S8 ). Several PPIs captured in this network have been described in previous studies, or have been reported in interaction databases ( Table S8 ) (51, 52, 58, 70, 71), though we capture a number of novel interactors as well. The most interconnected A3 interacting proteins were RNA binding proteins including proteins involved in splicing, ribonucleoprotein complexes (RNP), and RNA modification.…”
Section: Resultsmentioning
confidence: 99%
“…If a protein had more than one BP and one CC, the term with a larger population was selected to represent it in the network ( Table S8 ). Several PPIs captured in this network have been described in previous studies, or have been reported in interaction databases ( Table S8 ) (51, 52, 58, 70, 71), though we capture a number of novel interactors as well. The most interconnected A3 interacting proteins were RNA binding proteins including proteins involved in splicing, ribonucleoprotein complexes (RNP), and RNA modification.…”
Section: Resultsmentioning
confidence: 99%
“…If a protein had more than one BP and one CC, the term with a larger population was selected to represent it in the network ( Supplemental Table S8 ). Several PPIs captured in this network have been described in previous studies, or have been reported in interaction databases ( Supplemental Table S8 ) ( 51 , 52 , 58 , 70 , 71 ), although we capture a number of novel interactors as well. The most interconnected A3 interacting proteins were RNA binding proteins including proteins involved in splicing, ribonucleoprotein complexes (RNP), and RNA modification.…”
Section: Resultsmentioning
confidence: 99%
“…We did not detect any interaction between A3B and G3BP1, verifying that A3B immunoprecipitation did not precipitate the full SG structures. It is worth noting that PABPC1, DDX3, SAF-A, and MATR3 have been also identified in several published proteomic data sets of A3B pulldown from different cell lines 61,75,76 . Finally, we monitored the localization of these five A3B-interacting proteins after SeV infection via immunofluorescence.…”
Section: Identification Of An Apobec3b-interacting Complexmentioning
confidence: 90%